Managing time to attend concert rehearsals, ensemble practices and performing group classes among music students at the UiTM Faculty of Music / Faiha Farihah Senapi - Senapi, Faiha Farihah (Faculty of Music, 2016)
Effective time management allows individuals to plan their activities as per their priorities. The issues regarding time management among music students often point towards making decisions about which tasks get accomplished first and for music students this means juggling between academic tasks and musical activities such as practice and rehearsals. This study investigated 80 music degree students from the Faculty of Music at Universiti Teknologi Mara by distributing a survey questionnaire designed to look at students' perceptions towards the importance, usefulness, enjoyment and commitment to attend concert rehearsals, ensemble practice sessions and performing group classes. Factors influencing music students' absences from concert rehearsals, ensemble practice sessions and performing group classes and methods of overcoming the problems related to concert rehearsals, ensemble practice sessions and performing group classes' attendance were also investigated. Findings from the study showed that most of the students were missing their rehearsals, practices and classes due to their health issues.